2004
DOI: 10.1164/rccm.200207-765oc
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Secretion by Cystic Fibrosis Airway Epithelial Cells

Abstract: It is controversial whether mutations in cystic fibrosis transmembrane conductance regulator intrinsically dysregulate inflammation. We characterized passage 2 human tracheobronchial epithelial cell cultures morphologically and physiologically and determined whether cytokine production or nuclear factor-kappaB activation was systematically altered in cystic fibrosis (CF) cells. Non-CF and CF cells originating from a total of 33 and 25 lungs, respectively, were available for culture on plastic or at an air-liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
93
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 37 publications
17
93
5
Order By: Relevance
“…However, conflicting results have been reported on whether CF airways undergo proinflammatory response in the absence of bacterial infections (14 -16). Several studies have shown that both cytokine profile secretion and NF-B activation are similar in CF and normal cells (17,18). However, mounting evidence suggests that inflammation may occur before infection, and CFTR-defective cells have an intrinsically proinflammatory phenotype (19 -23).…”
Section: Ystic Fibrosis (Cf)mentioning
confidence: 99%
“…However, conflicting results have been reported on whether CF airways undergo proinflammatory response in the absence of bacterial infections (14 -16). Several studies have shown that both cytokine profile secretion and NF-B activation are similar in CF and normal cells (17,18). However, mounting evidence suggests that inflammation may occur before infection, and CFTR-defective cells have an intrinsically proinflammatory phenotype (19 -23).…”
Section: Ystic Fibrosis (Cf)mentioning
confidence: 99%
“…These cultures, derived from both animal and adult human cells, have been instrumental in increasing our knowledge of epithelial cell physiology (10) and responses to insults such as bacterial and viral infection (11,12). The establishment of a novel welldifferentiated primary bronchial epithelial cell (WD-PBEC) model using epithelial cells from children would therefore be useful in addressing these issues in childhood asthma.…”
mentioning
confidence: 99%
“…Agonist stimulation of TLR2 causes RE cells to produce IL-6 and IL-8 (16,44), suggesting that TLR2-mediated signals in RE cells regulate the immune response by regulating the production of various chemokines and cytokines. In our experiments, treatment of RE cells with TLR2 agonists induced the production of MIP-1a, MCP-1, and IP-10, stimulating the recruitment of inflammatory cells into the lungs during BIPF.…”
Section: Discussionmentioning
confidence: 99%